Incentivos laborales para el incremento en la productividad de las empresas del sector de telecomunicaciones (2017)
In the present monograph, a contextualization of key elements to develop the proposed theme is given in the first instance. Through the development of the content, it is intended to determine the influence of work incentives on labor productivity in a Colombian telecommunications company. To achieve this objective, a brief introduction to the different existing theories that refer to the models of work motivation is presented. This section of the work exposes the most appropriate motivation mechanisms adopted by the service marketing industry in Colombia and its transformation over the years to what is currently accepted by the international community.